Aktivitas Antibakteri Kulit Buah Karika Dieng terhadap Shigella flexneri dan Escherichia coli - Novalina, Dhiah; Sugiyarto, Sugiyarto; Susilowati, Ari (Jurnal Teknologi Laboratorium, 2018)
Karika is an endemic plant of Dieng Plateau. The leaf of Karika has been studied to have antibacterial activity against bacteria that cause diarrhea, while the peels are removed or used as a mixture of animal feed. This study aims to determine the antibacterial activity of Karika peels against bacteria that cause poisoning, i.e Shigella flexneri, and Escherichia coli. The sample fractionated to obtain the fraction of n-hexane and ethyl acetate. The fractions were tested for their antibacterial activity against Shigella flexneri and Escherichia coli by the cup-plate method. The results showed that the ethyl acetate fraction (ethyl acetate 50%) had the highest inhibition on Shigella flexneri and Escherichia coli compared with another concentration. Based on the study can be concluded that the peels of Karikahas antibacterial activity against Shigella flexneri and Escherichia coli.